Breastfeeding Education for Pregnant Women with Chronic Energy Deficiency in Celebrating World Breastfeeding Week 2024 in Sidoarjo, Indonesia - Suprihatin, Kusmini; Fildzah Ayu; Siti Maemonah; Loetfia Dwi Rahariyani; Alfi Maziyah; Riza Retnaini; Septi Ulfiana Rohmatin; Ivonne; Ingenta Nandi; Rony AP Tamba; Mika Yudistia; Hikmah Kurniasari; Ningsih, Nurhidayati; Aini, Nur (Frontiers in Community Service and Empowerment, 2025)
Introduction: Nutrition during pregnancy plays an important role in maternal health and fetal development. Lack of protein energy (KEP) in pregnant women can lead to a variety of health complications, including low birth weight (BBLR) and premature birth. This community service aims to provide health counseling on the effectiveness of education about breastfeeding in pregnant women. Methods: Data were collected using a descriptive approach with data obtained from two main sources: frequency distribution of demographic characteristics of extension participants (age and education level) and the results of breastfeeding education evaluation. A total of 50 mothers consisting of health cadres and pregnant women participated in counseling and evaluation activities. Results: The results showed that the majority of participants were aged 20 to 40 years (60%) with a high school level of education (48%). All participants (100%) felt that breastfeeding education activities were useful and needed to be provided continuously. Discussion: Breastfeeding counseling and education activities were considered positive by the participants and to increase the effectiveness of teaching methods so that the understanding of breastfeeding material can be more optimal, a further education program with a more interactive and personalized approach is needed for a better understanding among pregnant women, especially related to the importance of breastfeeding and correct breastfeeding techniques.